Meta-analysis on the efficacy of behavioral, information and economic interventions in increasing energy-efficiency adoption among households - Tarun M. Khanna; Diana Danilenko; Lukas Tomberg; Sven Hansteen; Mark Andreas Andor; Paul Lohmann; Jan C. Minx (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Energy efficiency is often cited as a critical component of mitigation pathways that avoid the worst effects of climate change but suffers from chronic underinvestment. This paper evaluates the efficacy of a range of voluntary approaches-monetary incentives, information and behavioral interventions-on the willingness of households to pay for energy efficient appliances, the market share of efficient appliances, and the subsequent savings in energy consumption to understand which interventions work, under what conditions, and why. We find that information provision, labeling, rebates and subsidies increase willingness to pay for efficient appliances moderately, while loans are ineffective. The effects of such interventions on market shares and associated rebound effects on energy consumption of purchase of energy-efficient appliances remain unclear given the limited evidence. Closing this should be a priority to facilitate better understanding of the role of such interventions in climate and energy policy. Real-world effects are also likely to be smaller than those reported due to study design limitations and potential reporting biases. Overall, the existing evidence does not strongly support the effectiveness of these interventions in achieving large-scale energy efficiency improvements required for decarbonization. – – Energieeffizienz wird oft als kritische Komponente von Klimaschutzmaßnahmen genannt, die die schlimmsten Auswirkungen des Klimawandels vermeiden sollen, leidet aber unter chronischer Unterinvestition. In diesem Papier wird die Wirksamkeit einer Reihe freiwilliger Ansätze - monetäre Anreize, Informationen und Verhaltensmaßnahmen - auf die Bereitschaft der Haushalte, für energieeffiziente Geräte zu zahlen, den Marktanteil effizienter Geräte und die daraus resultierenden Einsparungen beim Energieverbrauch untersucht, um zu verstehen, welche Maßnahmen unter welchen Bedingungen und warum funktionieren. Wir stellen fest, dass die Bereitstellung von Informationen, die Kennzeichnung, Rabatte und Subventionen die Bereitschaft, für effiziente Geräte zu zahlen, mäßig erhöhen, während Kredite unwirksam sind. Die Auswirkungen solcher Maßnahmen auf die Marktanteile und die damit verbundenen Rebound-Effekte auf den Energieverbrauch beim Kauf energieeffizienter Geräte bleiben angesichts der begrenzten Evidenz unklar. Die Schließung dieser Lücke sollte eine Priorität sein, um ein besseres Verständnis der Rolle solcher Interventionen in der Klima- und Energiepolitik zu ermöglichen. Aufgrund von Einschränkungen beim Studiendesign und möglichen Verzerrungen bei der Berichterstattung sind die Auswirkungen in der Realität wahrscheinlich geringer als berichtet. Insgesamt sprechen die vorliegenden Erkenntnisse nicht eindeutig für die Wirksamkeit dieser Maßnahmen, wenn es darum geht, die für die Dekarbonisierung erforderlichen groß angelegten Energieeffizienzsteigerungen zu erreichen.
Keywords: Q58; Q48; D11; D83; 330; Energy efficiency; meta-analysis; energy conservation; behavioral interventions; economic incentives; policy instruments